The pattern change of hepatitis B virus genetic diversity in Northwestern Tanzania - Mathias Mlewa; Shimba Henerico; Helmut A. Nyawale; Ivon Mangowi; Aminiel Robert Shangali; Anselmo Mathias Manisha; Felix Kisanga; Benson R. Kidenya; Hyasinta Jaka; Semvua B. Kilonzo; Britta Groendahl; Philipp Koliopoulos; et al. (Scientific Reports)
Abstract Hepatitis B virus genetic diversity (HBV) evaluation is scarcely done in Tanzania, imposing a crucial knowledge gap toward elimination of HBV infection by 2030. This cross-sectional study was conducted on purposively selected 21 plasma samples with high HBV-deoxyribonucleic acid (DNA) levels of > 300,000IU/mL. DNA extraction was done using Qiagen DNA Blood Mini Kit (Qiagen, Hilden, Germany). Partial amplification of 423 bp of pol gene, sequencing and analysis; and statistical analysis by STATA version 15 were done. These patients had mean age of 41 ± 11 years with HBV-DNA median of 979 [185.5–8457.5] IU/mL. The genotypes detected were HBV/A; 76.2% (16/21), HBV/D; 19% (4/21), and lastly HBV/G; 4.8% (1/21). Most of the HBV/As and all of the HBV/Ds identified in this study did not cluster with HBV/As and HBV/Ds from other parts of the world. Overall, 19% (4/21) of the patients had HBV escape mutations (T123V, Y134N, P120T and T123A). In conclusion, HBV/A and HBV/D are predominant over time in North-western Tanzania. Most HBV/A and all HBV/D are unique to Tanzania as had been previously reported. However, the pattern of hepatitis B virus genetic diversity is changing in Northwestern Tanzania with occurrence of HBV/G as new genotype in the region.